Penerapan Differential Reinforcement of Alternative Behavior dalam Mereduksi Perilaku Adiksi Smartphone di SMP Negeri 51 Surabaya - Habsy, Bakhrudin All; Zahro, Putri Awalia; Mustika, Erika Winda; Nafisah, Durrotun (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Smartphones in the digital age are an inseparable object in everyday life. Both parents and children are its users. The use of smartphones if not used wisely will have a negative impact, one of which is addiction. Smartphone addiction is also often found in the school environment, due to the lack of self-control and time management skills so that it disrupts their activities. This results in problems such as withdrawal, decreased direct or face-to-face interaction, decreased grades, lack of focus and making individuals less sensitive to the surrounding environment. The method used in this community service uses qualitative with the type of guidance and counseling action research (PTBK) using differential reinforcement of alternative behavior techniques. The selection of the technique aims to reduce unwanted behavior by replacing other alternative behaviors that are based on the interest of students. Other alternatives that are considered capable of reducing these behaviors such as reading books, paskibraka, hanging out with friends, and also cooking activities. The results of the community service obtained that the differential reinforcement of alternative behavior technique is effectively applied to junior high school children to reduce smartphone addiction with changes according to the desired target.